Cosmetovigilance: “Beautiful Is Pain” - Mochamad Yusuf Zainudin; Luthfi Chabib (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2023)
Cosmetics are defined as preparations used on the skin, mouth, nails, hair and eyes with the aim of increasing attractiveness, providing fragrance or protection of body odor, cleaning. The difference between drugs and cosmetics is sometimes not clear. Regulations covering cosmetic products that discuss the products used are safe and can be used by healthy people, product safety, and efficacious from cosmetic products approved by national authorities before being sold to consumers. Monitoring the safety of cosmetic products, and is a very important component of public health activities. After sales supervision of cosmetic products must be widely spread in the community, and problems related to these products can be solved, and identified in order to achieve a safe product. In August 2022, a search for the term cosmetovigilance in the Google search database returned 38 articles Family physicians and expert care practitioners, have a very useful role in providing an understanding of Adverse Drug Reactions (ADRs) caused by cosmetic products, and with such occurrences they can encourage patients to report Adverse Drug Reactions (ADRs) to the appropriate officials. authorized. Raise awareness of the new concept and become valuable commentary on public health at large.